PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXPLICIT INSTRUCTION (EI) TERHADAP HASIL BELAJAR MAHASISWA TINGKAT II PADA MATA KULIAH PELAYANAN KELUARGA BERENCANA (KB) DI STIKES RANAH MINANG PADANG - Wuri Komalasari (PAKAR Pendidikan, 2015)
Cooperative learning model Explicit Instruction (EI) is a direct instructional model specifically designed to develop students' comprehension of procedural and declarative knowledge that can be taught with the step-by-step pattern. Based on the results of student learning in the subject of family planning services, the average score for each score is as follows: A (14.12%), B (69.41%), C (12.94%), and D (3.52%). This illustrates that there are still some students who get less optimal score. This study aims to determine the effect of Cooperative Learning Model Explicit Instruction (EI) to the students’ learning outcomes of level II in STIKes Ranah Padang Minang. This research is experimental. The population of this study is all second level students of STIKes Ranah Minang Padang (112 students). The sample selection is done through purposive sampling. The class selected to be the sample is class A as the experimental class and class B as the control class. This research was conducted in STIKes Ranah Minang Padang for 2 weeks beginning on July 1 to July 12, 2014. The results showed that learning outcomes’ achievement in the experimental class was higher than those in the control class. This was evident from the difference in the average of posttest experimental score where the experimental class gained up to 80.60 while the control class gained 70.90. After all, it was obtained that the thitung = 5.636 and ttable = 1.994. Because thitung 5.636 ˃ ttable = 1.994, then the hypothesis is accepted. From the research, it can be concluded that the application of cooperative learning model Explicit Instruction (EI) impacts on the student learning outcomes in Family Planning (FP) subject. It is expected that the lecturers will employ the cooperative learning model Explicit Instruction (EI) in Family Planning (FP) subject and other subjects.